The Lockean Influence on Newman's Epistemology An Historical Analysis Describing Newman's Engagement with Locke's Ideas - Walker, Becky (2019)
This article discusses John Locke's positive contribution to Newman's epistemology throughout the latter's career. Beginning with one of Newman's earliest published works, his Essay on Miracles, he borrowed and further developed ideas from Locke's A Discourse on Miracles regarding the necessity of miracles to validate the Christian message and the personal nature and cumulative method of weighing evidence. Later, in Newman's most mature epistemological work, An Essay in Aid of a Grammar of Assent, one can discern Locke's influence on Newman's views on the weaknesses of deductive logic, the personal nature of knowledge, and the role of connecting ideas to arrive at knowledge.
Keywords: Locke; Newman; Knowledge; Logic; Probability